Enhancing Immune Responses to a DNA Vaccine Encoding Toxoplasma gondii GRA7 Using Calcium Phosphate Nanoparticles as an Adjuvant - Sun, Hong-Chao; Huang, Jing; Fu, Yuan; Hao, Li-Li; Liu, Xin; Shi, Tuan-Yuan (Frontiers in Cellular and Infection Microbiology, 2021)
Toxoplasma gondii (T. gondii) infects almost all warm-blooded animals, including humans. DNA vaccines are an effective strategy against T. gondii infection, but these vaccines have often been poorly immunogenic due to the poor distribution of plasmids or degradation by lysosomes, it is necessary to evaluate the antigen delivery system for optimal vaccination strategy. Nanoparticles (NPs) have been shown to modulate and enhance the cellular humoral immune response. Here, we studied the immunological properties of calcium phosphate nanoparticles (CaPNs) as nanoadjuvants to enhance the protective effect of T. gondii dense granule protein (GRA7). BALB/c mice were injected three times and then challenged with T. gondii RH strain tachyzoites. Mice vaccinated with GRA7-pEGFP-C2+nano-adjuvant (CaPNs) showed a strong cellular immune response, as monitored by elevated levels of anti-T. gondii specific IgG, a higher IgG2a to IgG1 ratio, elevated IL-12 and IFN-γ production and low IL-4 levels. We found that a significantly higher level of splenocyte proliferation was induced by GRA7-pEGFP-C2+nano-adjuvant (CaPNs) immunization, and a significantly prolonged survival time and decreased parasite burden were observed in vaccine immunized mice. These data indicated that CaPNs-based immunization with T. gondii GRA7 is a promising approach to improve vaccination.